Pengaruh Partisipasi Penganggaran dan Penekanan Anggaran Pada Senjangan Anggaran Dengan Locus of Control Sebagai Pemoderasi - Ayounik Mahasabha, Ni Luh; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi; Vol 26 No 3 (2019)DO - 10.24843/EJA.2019.v26.i03.p17, 2019)
The purpose of this study is to examine empirically the ability of internal locus of control in moderating the influence of budgeting participation and budget emphasis on budgetary slack. This research was conducted in 37 Badung District Regional Organizations. The number of samples taken was 111 using the purposive sampling method. Data collection was done through questionnaire. The analysis technique used is the absolute value of the difference.. Based on the results of the analysis, it was found that internal locus of control weakened the effect of budgetary participation on budgetary slack. It is shows that the higher budgeting participation causes the higher budgetary slack and will decrease if there is an internal locus of control. However internal locus of control variable does not moderate the effect of budget emphasis on budgetary slack. Keywords: Budgeting participation, budget emphasis, internal locus of control, budgetary slack